Smart Starter Remote Control (SSRC) / Muhamad Rizuwan Yahir@Yahaya and Moiid Azwan Ahmad - Yahir@Yahaya, Muhamad Rizuwan; Ahmad, Mohd Azwan (2002)
This is the project where we use the remote to start the motorcycle. However, it called a “Smart Starter Remote Control” (SSRC) because the starter is using a remote control in its operation. People can use a remote control or conventional way to start the motorcycle. For safety, the user must insert key within 300 second, if not the engine will ‘OFF’ automatically. We build this project based on our experienced as a student that always hurry to attend our class when we wake up late in the morning. Moreover, the point is this “Smart Starter Remote Control” can save our time. Its also can be implement to other things, for example car, electrical equipment in house and many things